Legal Liability Of Defaulting Winners In Voluntary Auctions - Komang Rama Agastya; Anak Agung Istri Agung; Nengah Renaya (UNIVERSITAS PAKUAN, 2026)
Voluntary auctions under Minister of Finance Regulation (PMK) No. 122/PMK.06/2023 demand strong legal certainty and efficient procedures. A highest bidder's failure to pay within five working days constitutes default, triggering swift legal consequences. This normative study uses statutory and conceptual approaches to fill key research gaps unclear consequences for defaulting winners in voluntary auctions and ambiguous status of second-highest bidders. The novelty lies in analyzing norm conflicts between PMK's automatic sanctions (deposit forfeiture, award cancellation) and Civil Code (KUHPerdata) Article 1243 damage claims, providing fresh harmonization insights. Findings show defaulting winners lose auction approval and full Auction Bid Security Deposit (UJPL), split 50% to state revenue and 50% to sellers. PMK allows mitigations like re-auctions or rolling buyers (up to third bidder with consent), but sellers can pursue civil claims for uncovered losses like value drops. Second-highest bidders hold conditional positions they must accept explicitly, meet limit values or gain seller approval, and receive protections including deposit refunds and timely notifications. This prevents automatic substitution while ensuring fairness and efficiency against third-party defaults. Keywords : Voluntary Auction, Default, Highest Bidder.